Preparation method and application of cadmium sulfide nanotube array catalyst
The morphology of cadmium sulfide is regulated by photoetching nanoarray method, and a cadmium sulfide nanotube array catalyst with a large specific surface area was prepared, which solved the problem of low efficiency of existing photocatalysts and achieved efficient photoelectric catalytic decomposition of water to produce hydrogen.
Patent Information
- Application Number
- CN202510293987.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-13
AI Technical Summary
The existing photocatalysts have problems such as wide band gap, low solar energy utilization rate, and high carrier recombination rate, which limits their efficiency in photoelectric catalytic decomposition of water to produce hydrogen.
The morphology of cadmium sulfide is regulated by a new photoetching nanoarray method, and a cadmium sulfide nanotube array catalyst with a large specific surface area was prepared to increase the active area of the photoelectrocatalytic reaction and inhibit the recombination of photogenerated carriers.
The purpose of improving the efficiency of hydrogen production by photoelectro-catalytic decomposition of water is achieved, and the recombination reaction is effectively suppressed by increasing the active area and promoting the separation and transmission of photogenerated carriers.
Smart Images

Figure CN119793487A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic photoelectric materials, and specifically relates to a preparation method of a cadmium sulfide nanotube array catalyst and a photoelectric catalytic application thereof. Background Art
[0002] In recent years, with the rapid development of social economy and the increasing demand for energy, energy and environmental issues have become two hot issues of widespread concern in the world. Therefore, the development and utilization of efficient and clean energy is imminent. For example, the photoelectrocatalytic water decomposition technology driven by solar energy to produce hydrogen using semiconductor photoelectrode materials has attracted widespread attention.
[0003] The key to photoelectrocatalytic water splitting technology is the construction of photoelectrode materials, which are usually composed of semiconductor photocatalytic materials as photocatalysts for photoelectrocatalytic water splitting technology. However, current photocatalysts still have problems such as wide band gap, low solar energy utilization, and high carrier recombination rate. Cadmium sulfide (CdS) semiconductor material has a relatively narrow band gap and is an important visible light responsive photocatalytic material. In view of these unique advantages of cadmium sulfide, it has been used to construct semiconductor photoelectrodes for photoelectrocatalysis and photocatalytic water splitting to produce hydrogen. However, the higher photogenerated carrier recombination rate limits its efficiency in producing hydrogen from photoelectrocatalytic water.
[0004] Photolithography is a common method for surface treatment of semiconductor catalysts, which can improve the photocatalytic performance to a certain extent. The photolithography technology used in the prior art is often single-wavelength laser etching, which cannot make good use of the auxiliary effect of photogenerated electrons and holes on surface etching. At present, there is no new method for photolithography of nano-array catalysts that produces better technical effects.
[0005] In view of the above problems, the present invention uses a new photolithography nanoarray method to control the morphology of cadmium sulfide, prepares a cadmium sulfide nanotube array catalyst with a large specific surface area, increases the active area of the photoelectrocatalytic reaction, and effectively inhibits the recombination of photogenerated carriers to improve the efficiency of photoelectrocatalytic water decomposition to produce hydrogen. Therefore, exploring a cadmium sulfide morphology with a high specific surface area and its corresponding preparation method is an important way to improve the efficiency of cadmium sulfide photoelectrocatalytic water decomposition to produce hydrogen. Summary of the invention
[0006] In view of the deficiencies of the above-mentioned prior art, the object of the present invention is to provide a method for preparing a cadmium sulfide nanotube array catalyst. The nanotube array catalyst prepared by the preparation method provided by the present invention can increase the specific surface area of the photoelectrocatalytic reaction excited by visible light, quickly separate and transmit photogenerated electron-hole pairs, and effectively inhibit the recombination of photogenerated carriers, thereby ultimately achieving the purpose of improving its photoelectrocatalytic water decomposition efficiency to produce hydrogen.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: A method for preparing a cadmium sulfide nanotube array catalyst comprises the following steps: Step 1: Preparation of CdS nanorod arrays using a simple one-step hydrothermal method (1) dispersing cadmium nitrate, thiourea and glutathione in deionized water at a molar ratio of (1-1.5):(1-1.5):(0.5-1), and stirring at room temperature to prepare a precursor mixture; (2) Clean and degrease the conductive glass, and perform ultrasonic treatment in anhydrous ethanol, acetone, isopropanol, and deionized water in sequence, and dry the glass; (3) adding the conductive glass treated in step (2) to the precursor mixture obtained in step (1), placing the mixture in a reaction kettle, and performing a hydrothermal reaction at a reaction temperature of 180-220° C. for a reaction time of 5-10 h; (4) After the reaction is complete, the conductive glass obtained in step (3) is cooled to room temperature, washed with deionized water, and transferred to a vacuum oven at 60-90° C. for drying for 2-5 hours to obtain the cadmium sulfide nanorod array; Step 2: Preparation of CdS nanotube arrays using photolithography First, the cadmium sulfide nanorod array obtained in step one is added to an etching solution, wherein the etching solution is a mixed aqueous solution of sodium hydroxide and sodium carbonate; then, the cadmium sulfide nanorod array sample immersed in the etching solution is irradiated with visible light for 2-5 hours; finally, the sample is taken out, washed and dried to obtain a cadmium sulfide nanotube array catalyst.
[0008] Preferably, in step 1, the molar ratio of cadmium nitrate, thiourea and glutathione is (1.1-1.4): (1.1-1.4): (0.6-0.8); Further preferably, in step 1, the molar ratio of cadmium nitrate, thiourea and glutathione is 1.2:1.2:0.72.
[0009] Preferably, in the hydrothermal reaction of step 1 (3), the reaction temperature is 190-210° C. and the reaction time is 8-10 h; More preferably, in the hydrothermal reaction of step 1 (3), the reaction temperature is 200° C. and the reaction time is 8 h.
[0010] Preferably, in step 2, the molar ratio of sodium hydroxide to sodium carbonate is (0.1-0.2):(0.2-0.5).
[0011] Further preferably, in step 2, the molar ratio of sodium hydroxide to sodium carbonate is 0.15:0.4.
[0012] Preferably, in step 2, the optical power of the visible light incident on the sample surface is 120-200 mW / cm2.
[0013] Further preferably, in step 2, the optical power of the visible light incident on the sample surface is 150 mW / cm2.
[0014] Preferably, the visible light irradiation time in step 2 is 2-4 h, more preferably 3 h.
[0015] A cadmium sulfide nanotube array catalyst is prepared according to the preparation method.
[0016] According to the above-mentioned cadmium sulfide nanotube array catalyst, a photoelectrocatalytic material is used for photoelectrocatalytic decomposition of water to produce hydrogen.
[0017] Characterization Instruments The crystal structure of the prepared samples was tested by Ultima U X-ray diffractometer (XRD) of Rigaku Corporation. The element distribution and valence state of the prepared samples were analyzed by ESCALAB 250XI X-ray photoelectron spectrometer (XPS) of Thermo Fisher Scientific, USA, with the signal of carbon with binding energy of 284.8 eV as reference. The morphology of the prepared samples was characterized by S-4800 field emission scanning electron microscope (SEM) of Hitachi, Japan and JEM-2100Plus transmission electron microscope (TEM) of JEOL. The light absorption characteristics of the prepared samples were analyzed by LAMBDA-950 UV-visible near-infrared spectrophotometer of PE Company, USA.
[0018] Photoelectric response test The photoelectric response characteristics of the prepared samples were tested by Shanghai Chenhua CHI760e electrochemical workstation. In the unbiased three-electrode system, the prepared sample was used as the working electrode, the platinum wire was used as the counter electrode, and the silver / silver chloride electrode was used as the reference electrode. The electrolyte used was a mixed solution of 0.25 M Na2SO3 and 0.35 M Na2S. Argon was passed into the electrolyte for 20 min before the test to remove the dissolved oxygen in the electrolyte.
[0019] Photoelectrocatalytic hydrogen production test The photoelectrocatalytic hydrogen production activity of the prepared samples was tested in a side-radiated sealed reaction cell equipped with a calibrated hydrogen collection tube. For a typical photoelectrocatalytic hydrogen production process, 200 ml of deionized water containing sacrificial agents (0.25 M Na2SO3 and 0.35 M Na2S) was added to the reaction cell, where S2- / SO32- ions acted as hole scavengers. The size was 1.5 A 2.0 cm2 sample was used as the working electrode, a platinum wire as the counter electrode, and a silver / silver chloride electrode as the reference electrode. The three electrodes were connected to the reaction cell, and the reaction cell was connected to a bias-free three-electrode system. A 300 W xenon lamp was selected as the light source, and a UV cutoff filter (λ≥400 nm) was used to generate visible light irradiation. The light emitted by the xenon lamp was vertically irradiated onto the sample electrode through the quartz window on the side of the reaction cell. At room temperature, the hydrogen produced in the closed reaction cell was collected into a scaled hydrogen collection tube using the drainage method, and the volume of hydrogen produced in the reaction cell was measured by the scale on the hydrogen collection tube.
[0020] Preparation principle: When cadmium sulfide nanorods are irradiated with visible light, the electrons in their valence band absorb photon energy and then jump to the conduction band, forming electron-hole pairs. After the electron-hole pairs migrate to the surface of the photoelectrode, they undergo redox reactions with a mixed solution of sodium carbonate and sodium hydroxide, resulting in photolithography. Since the axial part of the cadmium sulfide nanorods is not as stable as the side walls, the photolithography speed of the axial part is faster than that of the side walls. By adjusting the illumination time, cadmium sulfide nanotubes are formed.
[0021] Compared with the prior art, the present invention has the following advantages: (1) The present invention cleverly uses photolithography to combine the process of light-excited semiconductors generating electron-hole pairs with the alkaline etching reaction to regulate the morphology of cadmium sulfide nanoarrays and prepare cadmium sulfide nanotube array catalysts. Currently, there are no reports on the photocatalytic decomposition of water to produce hydrogen using cadmium sulfide nanotube arrays. (2) The present invention utilizes the excellent visible light absorption characteristics of cadmium sulfide to improve the utilization rate of light energy, and utilizes the tubular nanostructure with a large specific surface area to increase the active area of the visible photoelectrocatalytic reaction, effectively promote the separation and transmission of photogenerated carriers, and inhibit the recombination of photogenerated carriers; (3) The process of the present invention is simple, the purity of the synthesized material is high, the size is at the nanometer level, and the raw materials used are cheap, which is suitable for the field of photoelectrocatalytic water decomposition to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a schematic diagram of the preparation process of the cadmium sulfide nanorod and nanotube array catalyst prepared in Example 1 of the present invention.
[0023] Figure 2 This is the X-ray diffraction pattern of the cadmium sulfide nanorod and nanotube array catalyst prepared in Example 1 of the present invention.
[0024] Figure 3 The X-ray photoelectron spectrum of the cadmium sulfide nanotube array catalyst prepared in Example 1 of the present invention, (a) is the full spectrum, (b) is the fine spectrum of Cd, and (c) is the fine spectrum of S.
[0025] Figure 4 Transmission electron microscopy and high-resolution images of the cadmium sulfide nanotube array catalyst prepared in Example 1 of the present invention, (a) is a transmission electron microscopy image, and (b, c) are high-resolution transmission electron microscopy images.
[0026] Figure 5 These are scanning electron micrographs of the cadmium sulfide nanorod and nanotube array catalysts prepared in Example 1 of the present invention, (a, b) are scanning electron micrographs of the cadmium sulfide nanorod array, and (c, d) are scanning electron micrographs of the cadmium sulfide nanotube array catalyst.
[0027] Figure 6 The optical absorption spectrum and band gap diagram of the cadmium sulfide nanorod and nanotube array catalyst prepared in Example 1 of the present invention, (a) optical absorption spectrum, (b) band gap diagram.
[0028] Figure 7 The instantaneous photocurrent density curve and the linear scanning voltammetry curve of the cadmium sulfide nanorod and nanotube array catalyst prepared in Example 1 of the present invention, (a) is the instantaneous photocurrent density curve, and (b) is the scanning linear voltammetry curve.
[0029] Figure 8 The hydrogen production amount and hydrogen production rate curves of the cadmium sulfide nanorod and nanotube array catalyst prepared in Example 1 of the present invention, (a) hydrogen production amount graph, (b) hydrogen production rate curve graph.
[0030] Fig. 9 The X-ray diffraction patterns of CdS-1 and CdS-2 samples corresponding to Comparative Examples 1-2 of the present invention are shown in FIG.
[0031] Fig.10 These are scanning electron microscope images of the CdS-1 and CdS-2 samples corresponding to Comparative Example 1-2, (a, b) are scanning electron microscope images of the CdS-1 sample, and (c, d) are scanning electron microscope images of the CdS-2 sample.
[0032] Fig.11 The instantaneous photocurrent density and linear scanning voltammetry curves of the CdS-1 and CdS-2 samples corresponding to Comparative Example 1-2, (a) is the instantaneous photocurrent density curve, and (b) is the linear scanning voltammetry curve. DETAILED DESCRIPTION
[0033] In order to make the contents of the present invention easier to understand, the technical solutions of the present invention are further described below in conjunction with specific implementation methods. However, the embodiments are intended to explain the present invention and cannot be understood as limiting the present invention.
[0034] A method for preparing a cadmium sulfide nanotube array catalyst comprises the following steps: Step 1: Preparation of CdS nanorod arrays using a simple one-step hydrothermal method (1) dispersing cadmium nitrate, thiourea and glutathione in deionized water at a molar ratio of (1-1.5):(1-1.5):(0.5-1), and stirring at room temperature to prepare a precursor mixture; (2) Clean and degrease the conductive glass, and perform ultrasonic treatment in anhydrous ethanol, acetone, isopropanol, and deionized water in sequence, and dry the glass; (3) adding the conductive glass treated in step (2) to the precursor mixture obtained in step (1), placing the mixture in a reaction kettle, and performing a hydrothermal reaction at a reaction temperature of 180-220° C. for a reaction time of 5-10 h; (4) After the reaction is complete, the conductive glass obtained in step (3) is cooled to room temperature, washed with deionized water, and transferred to a vacuum oven at 60-90° C. for drying for 2-5 hours to obtain the cadmium sulfide nanorod array; Step 2: Preparation of CdS nanotube arrays using photolithography First, the cadmium sulfide nanorod array obtained in step one is added to an etching solution, wherein the etching solution is a mixed aqueous solution of sodium hydroxide and sodium carbonate; then, the cadmium sulfide nanorod array sample containing the etching solution is irradiated with visible light for 2-5 hours; finally, the sample is taken out, washed, and dried to obtain a cadmium sulfide nanotube array catalyst.
[0035] Example 1 Step 1: Preparation of CdS nanorod arrays using a simple one-step hydrothermal method (1) Preheat the constant temperature drying oven and set the temperature to 200 °C; (2) Use a measuring cylinder to measure 40 ml of deionized water and pour it into a beaker; (3) Weigh 1.2 mmol of cadmium nitrate tetrahydrate (0.3701 g) and pour it into a beaker. Place the beaker on a magnetic stirrer and stir for 10 minutes. (4) Weigh 1.2 mmol thiourea (0.0913 g) and pour it into a beaker. Place the beaker on a magnetic stirrer and stir for 10 minutes. (5) Weigh 0.72 mmol glutathione (0.2212 g) and pour it into a beaker. Place the beaker on a magnetic stirrer and stir for 30 minutes. (6) Place two FTO conductive glasses in the reactor tank at an angle, with the conductive surface facing down; (7) Pour 40 ml of reaction precursor solution into the inner tank and seal the reactor; (8) The reactor was placed in a constant temperature drying oven for 8 hours; (9) After the reaction is completed, the reactor is taken out, and the reactor is cooled to room temperature. The light yellow sample is taken out, rinsed with deionized water, and then placed in a constant temperature drying oven at 60 °C for 2 hours to obtain a cadmium sulfide nanorod array sample.
[0036] Step 2: Fabrication of CdS nanotube arrays using photolithography First, prepare the etching solution: use a measuring cylinder to measure 300 ml of deionized water and pour it into a beaker, then pour 0.15 M (1.8 g) of sodium hydroxide and 0.4 M (12.72 g) of sodium carbonate into the beaker in turn, stir for 30 minutes, and let stand for 24 hours. Second, the photolithography operation of the conductive glass with the cadmium sulfide nanorod arrays is as follows: (1) Pour 200 ml of etching solution into the reaction tank.
[0037] (2) Place the CdS nanorod array sample grown on FTO conductive glass vertically in the solution.
[0038] (3) Use a 300 W xenon lamp as the light source and use a UV cut-off filter to use only visible light. The incident light intensity needs to be measured and calibrated with an optical power meter to ensure that the light power incident on the sample surface is 150 mW / cm2.
[0039] (4) The CdS nanorod array was irradiated for 3 hours.
[0040] (5) After the irradiation, the sample was taken out, rinsed with deionized water, and then placed in a constant temperature drying oven at 60 °C for 2 hours to obtain a cadmium sulfide nanotube array catalyst.
[0041] The following are the composition, morphology characterization and photoelectrocatalytic water decomposition hydrogen production performance test results of the cadmium sulfide nanotube array catalyst prepared in the experimental example: Figure 1 The flow chart of the preparation of the cadmium sulfide nanotube array catalyst prepared in the embodiment of the present invention shows the process of preparing the cadmium sulfide nanotube array catalyst by using a novel photolithography method to control the morphology of the cadmium sulfide nanoarray based on the hydrothermal method.
[0042] Figure 2 It is an X-ray diffraction spectrum. As can be seen from the figure, the diffraction peaks of the prepared CdS nanorod array and CdS nanotube array match the hexagonal phase CdS of the standard card JCPDS (41-1049), and there are no impurity peaks in the sample, indicating that the prepared CdS has high purity.
[0043] Figure 3 The X-ray photoelectron spectrum shows that there are two elements, Cd and S, in the CdS nanotube array structure, proving the successful preparation of the CdS nanotube array structure.
[0044] Figure 4 Transmission electron microscopy and high-resolution images. Figure 4 As can be seen in (a), the axis of the CdS nanorod is etched to form a depression. Figure 4 Clear lattice fringes appear in the high-resolution transmission electron microscopy images shown in (b) and (c), corresponding to the (002) crystal plane of CdS.
[0045] Figure 5 The scanning electron microscope images show that the CdS nanorods (a, b) show a hexagonal columnar nanostructure; the CdS nanotubes (c, d) show that after photolithography, the nanorod axis is etched to form a tubular nanostructure.
[0046] Figure 6 Figure 2 is the optical absorption spectrum and band gap diagram. As can be seen from the figure, after CdS nanorods are etched into CdS nanotubes, the optical absorption intensity at a wavelength of 300-500 nm increases, the absorption edge is still 540 nm, and the band gap is still 2.34 eV.
[0047] Figure 7 The instantaneous photocurrent density curve and the linear scanning voltammetry curve are shown in Figure 2. Figure 7 The instantaneous photocurrent density curve shown in (a) shows that all the tested samples have very sensitive photoresponse characteristics. Among them, the photocurrent density of the CdS nanorod array is 1.0 mA·cm-2; after 3 hours of photolithography, the photocurrent density of the prepared CdS nanotube array increased significantly to 2.5 mA·cm-2, which is 2.5 times that of the CdS nanorod array; Figure 7 From the linear scanning voltammetric characteristic curve shown in (b), it can be seen that the photocurrent density of all samples increases with the increase of applied bias voltage, and the photocurrent density of the CdS nanotube array photoetched for 3 hours increases more significantly.
[0048] Figure 8 is the hydrogen production amount and hydrogen production rate curve. Figure 8 The curve of hydrogen production versus time shown in (a) shows that under continuous visible light irradiation for 2 hours, the hydrogen production per unit area of the CdS nanorod array and CdS nanotube array photoelectrodes is linearly correlated with the irradiation time, which indicates that the prepared sample electrodes have stable hydrogen production capabilities. Figure 8 From the hydrogen production rate curves of the CdS nanorod array and CdS nanotube array photoelectrodes shown in (b), it can be seen that the CdS nanotube array photoanode has a higher hydrogen production rate than the CdS nanorod array, which can reach 21.4 μmol·cm-2·h-1, which is 3.19 times that of the nanorod array (6.7 μmol·cm-2·h-1).
[0049] In addition, as a comparison, the influence of etching solution selection and lighting conditions was explored.
[0050] Comparative Example 1 uses the same conditions and parameters as Example 1. The difference between Comparative Example 1 and Example 1 is that a cadmium sulfide sample is obtained without light exposure under the same time and the same etching solution conditions. This sample is recorded as CdS-1.
[0051] Comparative Example 2 uses the same conditions and parameters as Example 1. The difference between Comparative Example 2 and Example 1 is that under the same time and the same light conditions, the etching solution is changed to 0.15 M sodium hydroxide solution to obtain a cadmium sulfide sample, which is recorded as CdS-2.
[0052] Based on Comparative Examples 1-2, it can be seen that: Fig. 9 The X-ray diffraction patterns of the CdS-1 and CdS-2 samples corresponding to Comparative Example 1-2 are shown in FIG. 1. As can be seen from the figure, the diffraction peaks of the prepared CdS-1 and CdS-2 samples match the hexagonal CdS of the standard card JCPDS (41-1049). Fig.10 The scanning electron microscope images of the CdS-1 and CdS-2 samples corresponding to Comparative Example 1-2 are shown in FIG. As can be seen from the figure, the scanning electron microscope images (a, b) of the CdS-1 sample show that the center of the cadmium sulfide nanorods is not etched without light. The scanning electron microscope images (c, d) of the CdS-2 sample show that after the etching solution is changed to sodium hydroxide, the nanorods are etched, but the damage is more serious, and a larger block structure appears.
[0053] Fig.11 The instantaneous photocurrent density and linear scanning voltammetry curves of CdS-1 and CdS-2 samples corresponding to Comparative Example 1-2 are shown in FIG. Fig.11 The instantaneous photocurrent density curve shown in (a) shows that all the tested samples have very sensitive light response characteristics. The photocurrent density of the CdS-1 sample without light conditions is not much different from that of the CdS nanorods; after replacing the etching solution with sodium hydroxide solution and photoetching for 3 hours, the photocurrent density of the prepared CdS-2 sample increased to 1.7 mA·cm-2. Fig.11 From the linear sweep voltammetric curves shown in (b), it can be seen that the photocurrent density of all samples increases with the increase of the applied bias voltage. Combined with Comparative Examples 1-2, the present invention shows that the center of the cadmium sulfide nanoarray catalyst rod prepared without light is not etched and cannot form nanotubes, and when the etching solution is single sodium hydroxide, the nanorods are severely damaged, and the photoelectrocatalytic reaction effect is not as good as when the etching solution is a mixture of sodium hydroxide and sodium carbonate and the etching is assisted by light conditions.
[0054] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a cadmium sulfide nanotube array catalyst, characterized in that: The steps include: Step 1: Preparation of CdS nanorod arrays using a simple one-step hydrothermal method (1) dispersing cadmium nitrate, thiourea and glutathione in deionized water at a molar ratio of (1-1.5):(1-1.5):(0.5-1), and stirring at room temperature to prepare a precursor mixture; (2) Clean and degrease the conductive glass, and perform ultrasonic treatment in anhydrous ethanol, acetone, isopropanol, and deionized water in sequence, and dry the glass; (3) adding the conductive glass treated in step (2) to the precursor mixture obtained in step (1), placing the mixture in a reaction kettle, and performing a hydrothermal reaction at a reaction temperature of 180-220° C. for a reaction time of 5-10 h; (4) After the reaction is complete, the conductive glass obtained in step (3) is cooled to room temperature, washed with deionized water, and transferred to a vacuum oven at 60-90° C. for drying for 2-5 hours to obtain the cadmium sulfide nanorod array; Step 2: Preparation of CdS nanotube arrays using photolithography First, the cadmium sulfide nanorod array obtained in step 1 is added into an etching solution, wherein the etching solution is a mixed aqueous solution of sodium hydroxide and sodium carbonate; Subsequently, the cadmium sulfide nanorod array sample immersed in the etching solution is irradiated with visible light for 2-5 hours; finally, the sample is taken out, washed, and dried to obtain a cadmium sulfide nanotube array catalyst.
2. The method for preparing a cadmium sulfide nanotube array catalyst according to claim 1, characterized in that: In step 1, the molar ratio of cadmium nitrate, thiourea and glutathione is (1.1-1.4): (1.1-1.4): (0.6-0.8).
3. The method for preparing a cadmium sulfide nanotube array catalyst according to claim 1, characterized in that: In step 1 (3), the reaction temperature of the hydrothermal reaction is 190-210° C. and the reaction time is 8-10 h.
4. The method for preparing a cadmium sulfide nanotube array catalyst according to claim 1, characterized in that: In step 2, the molar ratio of sodium hydroxide to sodium carbonate is (0.1-0.2): (0.2-0.5).
5. The method for preparing a cadmium sulfide nanotube array catalyst according to claim 1, characterized in that: In step 2, the optical power of visible light incident on the sample surface is 120-200 mW / cm2.
6. The method for preparing a cadmium sulfide nanotube array catalyst according to claim 1, characterized in that: The visible light irradiation time in step 2 is 2-4h.
7. A cadmium sulfide nanotube array catalyst prepared according to the method for preparing a cadmium sulfide nanotube array catalyst according to any one of claims 1 to 6.
8. Use of the cadmium sulfide nanotube array catalyst according to claim 7 as a photoelectrocatalytic material for photoelectrocatalytic decomposition of water to produce hydrogen.
Citation Information
Patent Citations
Cadmium sulfide two-dimensional nanorod array catalyst and preparation method and application of cadmium sulfide two-dimensional nanorod array catalyst
CN107537519A
Composite electrode material, as well as preparation method and application thereof
CN110760880A
CdS-g-C3N4 heterojunction photocatalytic hydrogen production catalyst and preparation method thereof
CN111495415A
Preparation method of cadmium sulfide / aluminum nano-photocatalyst
CN113908857A
Crystalline rare earth aluminum borates
US5043308A